2018
DOI: 10.1017/s109285291800113x
|View full text |Cite
|
Sign up to set email alerts
|

Drug–drug interactions and clinical considerations with co-administration of antiretrovirals and psychotropic drugs

Abstract: Psychotropic medications are frequently co-prescribed with antiretroviral therapy (ART), owing to a high prevalence of psychiatric illness within the population living with HIV, as well as a 7-fold increased risk of HIV infection among patients with psychiatric illness. While ART has been notoriously associated with a multitude of pharmacokinetic drug interactions involving the cytochrome P450 enzyme system, the magnitude and clinical impact of these interactions with psychotropics may range from negligible ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 238 publications
(420 reference statements)
0
28
0
Order By: Relevance
“…Protease inhibitors are extensively metabolized by the cytochrome P450 system and have been shown to interact with many drugs, including psychotropics. 53 The use of ritonavir may lead to increased concentrations of coadministered drugs that are CYP3A4 or CYP2D6 substrates or decreased concentrations of CYP1A2 or CYP2B6 substrates, many of which are psychotropics.…”
Section: Psychotropic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protease inhibitors are extensively metabolized by the cytochrome P450 system and have been shown to interact with many drugs, including psychotropics. 53 The use of ritonavir may lead to increased concentrations of coadministered drugs that are CYP3A4 or CYP2D6 substrates or decreased concentrations of CYP1A2 or CYP2B6 substrates, many of which are psychotropics.…”
Section: Psychotropic Considerationsmentioning
confidence: 99%
“…Owing to CYP450 enzyme or glucuronidation-inducing effects, ritonavir-boosted protease inhibitors also have been shown to lower concentrations of some psychotropics (e.g., bupropion, methadone, lamotrigine, and olanzapine), thus leading to increased dose requirements for these medications. 53 As most psychotropics are substrates for CYP isoenzymes, there are many additional theoretical interactions, but the clinical significance varies by agent. Clinicians should assess each potential interaction individually by reviewing available literature and manufacturer's prescribing information.…”
Section: Psychotropic Considerationsmentioning
confidence: 99%
“…Up to 10% of HIV-infected patients refuse to continue antiretroviral therapy because of its side effects (8,(10)(11)(12). Intolerability is frequently due to drug-drug interactions (DDIs), which increase the plasma concentrations of antivirals or coadministered medications (8,9,(13)(14)(15)(16)(17)(18)(19)(20). The molecular mechanisms responsible for this increased bioavailability are often unclear.…”
mentioning
confidence: 99%
“…Clinically significant interactions between mirtazapine and ritonavir-boosted lopinavir have not been reported. However, it is suggested that the lowest efficient dose of mirtazapine be used when it is co-administered with CYP3A4 inhibitors ( Goodlet, Zmarlicka, & Peckham, 2019 ). No interaction has been found between mirtazapine and hydroxychloroquine, chloroquine, ribavirin, and interferons.…”
Section: Methodsmentioning
confidence: 99%